Molecular genetics evidence for the in vivo roles of the two major NADPH-dependent disulfide reductases in the malaria parasite - Buchholz, Kathrin; Putrianti, Elyzana D.; Rahlfs, Stefan; Schirmer, Rolf Heiner; Becker, Katja; Matuschewski, Kai (The journal of biological chemistry, 2010)
Malaria-associated pathology is caused by the continuous expansion of Plasmodium parasites inside host erythrocytes. To maintain a reducing intracellular milieu in an oxygen-rich environment, malaria parasites have evolved a complex antioxidative network based on two central electron donors, glutathione and thioredoxin. Here, we dissected the in vivo roles of both redox pathways by gene targeting of the respective NADPH-dependent disulfide reductases. We show that Plasmodium berghei glutathione reductase and thioredoxin reductase are dispensable for proliferation of the pathogenic blood stages. Intriguingly, glutathione reductase is vital for extracellular parasite development inside the insect vector, whereas thioredoxin reductase is dispensable during the entire parasite life cycle. Our findings suggest that glutathione reductase is the central player of the parasite redox network, whereas thioredoxin reductase fulfils a specialized and dispensable role for P. berghei. These results also indicate redundant roles of the Plasmodium redox pathways during the pathogenic blood phase and query their suitability as promising drug targets for antimalarial intervention strategies.